INTANGIBLE AND INTEGRATED RESPONDING - Gogić, Nemanja (Ekonomija - teorija i praksa, 2022)
Compilation of non-financial and integrated reporting has arisen due to declining credibility and confidence in financial reporting, which have arisen due to the global economic crisis, blaming the growing number of accounting and company fraud in the last period, climate change, doubts about social and environmental implications globalization. The reaction to such an environment is the distrust of investors and other state holders in traditional financial reporting as well as the growing popularity of topics, corporate governance, sustainable development, corporate sustainability and integrated reporting. The paper presents the many advantages and limitations that companies face when compiling and presenting non-financial and integrated reporting, as the supreme framework for reporting.